Photoelastic Analysis of the Vertebral Fixation System Using Different Screws - Fakhouri, S. F.; Shimano, M. M.; Araujo, C. A.; Defino, H. L.; Shimano, A. C. (Engineering, Technology & Applied Science Research, 2012)
The purpose of this study was to compare using photoelasticity, the internal stresses produced by two types of pedicular screws (Synthes™) with three different diameters, when submitted to different pullout strengths. The fringe orders were evaluated around the screws using the Tardy compensation method. In all the models analyzed, the shear stress was calculated. Results showed that, independently of the applied load, the screw of smaller outer diameter had larger values of shear stress. According to the analysis realized, we observed that the place of highest stress was in the last thread, close to the head of the screws.